Penerapan Strategi Means-Ends Analysis melalui Model Pembelajaran Jigsaw untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Dian Wahyuni; Hepsi Nindiasari (Departement of Mathematics Education, 2025)
This research aims to determine the difference in the average increase in students' mathematical problem solving ability scores between the experimental class which was given the Means-Ends Analysis strategy through the Jigsaw learning model and the control class which received conventional learning for class X students at MAN 1 Cilegon City. The samples were selected from two classes using cluster random sampling technique. This type of research is quasi-experimental with a non-equivalent control group research design. The instrument used in this research was a test of mathematical problem solving abilities. The results of the research show that there are differences between classes that receive learning using the Means-Ends Analysis strategy through the Jigsaw learning model and classes that receive conventional learning. This is shown by the results of the independent sample t-test with a t-value of 2.480 and a p-value of 0.008. This can be confirmation that the Means-Ends Analysis strategy through the Jigsaw learning model has a significant influence on problem solving.